PENGARUH METODE PRAKTIKUM TERHADAP KEMAMPUAN ANALISIS SISWA DALAM MEMECAHKAN MASALAH PADA MATERI PENGUKURAN DI SMAN 5 JEMBER - Ahmad Nor Hamidy; Sudarti Sudarti; Lailatul Nuraini (Universitas Jember, 2022)
In the 21st century critical thinking skills are needed by students. Critical thinking skills have several indicators, including: interpretation, analysis, evaluation, inference, ability to explain and self regulation. In this research, the indicators that measured was analytical indicators. The purpose of this research is to determine the effect of practicum method on analytical skills. The research is an experimental research with post-test only control group design. The post-test questions used are 10 UN questions given at the end of te lesson. Location was at SMAN 5 Jember with research sample from class X1 and X4 wich were selected based on the smallest average value of midterm exam. The results of this research indicate that the practicum method has an effect on analytical skills’s student, it is known based on tested by non parametric Mann-Whitney U..